SCREENING AND PHYSIOTHERAPY SERVICES FOR MUSCULOSKELETAL COMPLAINTS IN THE ELDERLY DURING THE COVID-19 PANDEMIC AT TRESNA WERDHA WANA SOCIAL ORIGINAL SERAYA - Tri Adi Suparwati, Komang; Dhita Prianthara, I Made; Paramurthi, I.A Pascha; Astrawan, I Putu; Ayu Astiti Suadnyana, Ida; Prisa Jaya, I Putu; Sri Wahyuni Novianti, I Gusti Ayu (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The number of elderly people in Indonesia from year to year continues to increase. With the increasing amount of elderly, it is followed by an increase in musculoskeletal complaints. The outbreak of Covid-19 has resulted in limited and disrupted physical activity and health services for the elderly. The elderly are a group at risk of death if infected with Covid-19 because there is a degenerative process and there are co-morbidities. Community service activities carried out at the Tresna Werdha Wana Seraya Social Home in Ketalanggu Village aims to provide health services so that during the Covid-19 pandemic the quality of life for the elderly will be better. Activities carried out using blood pressure screening methods and examination of musculoskeletal complaints as well as providing physiotherapy services related to musculoskeletal complaints such as exercise and infrared therapy for free to the elderly. The participation in this community service activity was 34 people with the most aged 66-70 years. The results of this activity are the presence of the elderly, and the results of blood pressure screening and services for musculoskeletal complaints in the elderly at the Tresna Werdha Wana Seraya Social Institution during the Covid-19 pandemic.